The influence of sport climbing on depression and anxiety levels - literature review - Grzegorz Zieliński (Journal of Education, Health and Sport, 2018)
Introduction: Depression, as one of the most common psychological disorders, which is characterized by anxiety problems, lack of energy, feeling of worthlessness or self-esteem problems affects from 5 to 17% of the population. Despite the fact that it is such a vast problem, standard methods of treatment are usually unsatisfactory and relatively not universally accessible. For these reasons, it is crucial that some alternatives to traditional methods of depression treating, such as physical activity should be pursued.